Recent advances in detection of food allergens - Sharma, Nikunj; Upadhya, Ashutosh; Rafiq, Syed Mansha (Journal of Postharvest Technology, 2020)
Food allergy is an immunological reaction caused as a result of exposure of certain proteins or food allergens when administered in adequate amounts by sensitive people. Eight major food groups causing food allergy consist of cow’s milk, tree nut, fish, soy, peanut, wheat, hen’s egg and crustacean. Food allergens are the proteins that occur naturally in foods which may be responsible for abnormal immune responses. These allergies are either Immunoglobulin E(IgE)-mediated, non-Immunoglobulin E-mediated, immune complex-mediated or cell-mediated reactions. A number of detection methods used to identify and quantify the possible proteins responsible for allergenic properties exist which includes physicochemical methods such as kjeldahl nitrogen assay, colorimetry, electrophoresis, spectrophotometry, mass spectrometry and polymerase chain reaction methods (real time and conventional) and Immunological methods such as counter electrophoresis, immunoblotting, immunodiffusion, enzyme-linked immunosorbent assays (ELISAs), enzyme-linked immune spot assays (ELISPOTs) , radioimmunoassay to the newer ones i.e. immunodetection methods which include biosensor such as surface plasmon resonance (SPR).This review summarizes the novel detection methods used to identify and quantify these allergens.